2010
DOI: 10.1177/0091552110364999
|View full text |Cite
|
Sign up to set email alerts
|

The Community College Accountability Network: Understanding Institutional Accountability at Aspen Grove Community College

Abstract: This article reports on a qualitative, interpretive case study examining how trustees, administrators, faculty members, and staff members at a rural community college understand their institution's accountability environment. Data analysis and interpretation established that participants conceptualized institutional accountability as dialogic, involving ongoing communication with state authorities, employers, students, high schools, and universities about the formal and informal expectations assigned to the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…It is also consistent with federal policy agendas designed to promote degree completion. Indeed, within today’s cultural, political, and economic milieu, accountability may be a defining feature of legitimate public institutions (Alexander, 2000; Harbour, Davies, & Gonzales-Walker, 2010; Lattimore, D’Amico, & Hancock, 2012; Murphy, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…It is also consistent with federal policy agendas designed to promote degree completion. Indeed, within today’s cultural, political, and economic milieu, accountability may be a defining feature of legitimate public institutions (Alexander, 2000; Harbour, Davies, & Gonzales-Walker, 2010; Lattimore, D’Amico, & Hancock, 2012; Murphy, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Although a systematic analysis of the forces compelling DDDM in various educational sectors has not been undertaken, Ewell (2012) suggested that "colleges and universities [are] organizationally distinctive as settings for information use" (p. 2). Furthermore, data use and accountability efforts are shaped by local organizational and political contexts (Dougherty et al, 2011;Harbour, Davies, & Gonzales-Walker, 2010).…”
Section: Data-driven Decision Making In Educationmentioning
confidence: 99%
“…Long considered a relatively risk-free, peer-driven form of self-reflection, accreditation in the United States has in recent years become a compliance-driven component of an overall shift toward focusing on institutional effectiveness, student learning, and the completion agenda (Harbour, Davies, & Gonzales-Walker, 2010;Mullin, 2012). These changes have been and continue to be controversial as students, faculty, administrators, accrediting agencies, policymakers, and private interests express a myriad of sometimes conflicting interpretations as to what is needed and what is intended from accreditation.…”
mentioning
confidence: 99%